Strengthening reading literacy through contextual teaching and learning with Dayak Belusu local wisdom - Syahrul Syahrul; Shirly Rizki Kusumaningrum; Slamet Arifin; Adi Admoko; Siti Mas’ula (Universitas Papua, 2026)
This study aims to improve the reading literacy skills of elementary school students through the implementation of Contextual Teaching and Learning (CTL) integrated with the local wisdom of the Dayak Belusu community. Reading literacy in this research is defined as the ability to understand, interpret, and reflect on written texts at literal, inferential, and summarizing levels. The study employed Classroom Action Research (CAR) based on the spiral model of Kemmis and McTaggart, consisting of planning, acting, observing, and reflecting. The participants were fifth-grade students at SD Negeri 014 Tana Tidung, North Kalimantan. Data were collected through observation sheets, reading literacy tests, and teacher interviews, and analyzed using quantitative descriptive and qualitative techniques. The results of Cycle I showed that students’ reading literacy was still dominated by literal comprehension and that their participation in discussions was relatively low. After revising the learning strategy in Cycle II, student participation exceeded 80% on most indicators, and the average literacy test score increased from 58 to 76. Teacher interviews confirmed positive changes in cognitive, affective, and attitudinal aspects, including confidence, discipline, and cooperation. These findings indicate that CTL integrated with Dayak Belusu local wisdom effectively enhances reading literacy while strengthening cultural identity and positive character.